"The Study of Religion" and "Religious Studies": To What are We Entitled and to Whom are We Obliged? - Mulhern, Aldea (Religious studies and theology, 2019)
Here I offer thoughts on what the recent history of the academic study of religion might reveal about its current state, and why we need to continually renew attention to our collective, and ideally, contested, vision for the academy. I frame this reflection in relation to two scholars of religion, Donald Wiebe and Michel Desjardins, who in the late twentieth and early twenty-first centuries shaped the Canadian and American academic conversation about this field of study. I approach their work in this area not as discrete faits accompli, but as examples of iterative self-construction in the history of the field. Attention should continually be paid to what kind of religious studies we do, and what we study when we study religion; part of that account is of the we, specifically of our relationality, in our entitlements and obligations. I am increasingly persuaded that the key nexus of focus for our attention is not (or is no longer) primarily in the question of the humanistic versus the social-scientific study of religion. Thinking through what we do over against what we think we ought to be doing will involve a less oppositional, more relational accounting of and accounting for who we think we are and what we think we owe one another.